Six Sigma Roles for the Improvement of Company Manufacturing Processes and Waste Reduction (Journal of Academic Research, 2025)
A problem with an estimated annual loss of $50,000 was reported to a stator manufacturing company, so a Six Sigma team we formed and followed the Six Sigma steps to identify the root causes of the problem through its stages: identification, measurement, analysis process, and improvement and control stage, and indeed, the improvement will be implemented most effective in research by reducing production cost and developing the manufacturing process. Through Six Sigma tools, the root causes of the problem have already been identified, measured, and analysed using a range improved and controlled. So, the results of the study have identified the root causes of the problem which have represented improvements in reducing process wire loss from stator manufacturing , compensate for the differentiation of define, measure, analysis, improve, control phase. A actual company’s case study is performed in support of the reported wire loss by Green Belt Team.